Determination of Potential Scaffolds for Human Choline Kinase α1 by Chemical Deconvolution Studies. Issue 11 (28th June 2013) - Sahún‐Roncero, María; Rubio‐Ruíz, Belén; Conejo‐García, Ana; Velázquez‐Campoy, Adrián; Entrena, Antonio; Hurtado‐Guerrero, Ramon
<x xml:space="preserve">Abstract</x> Dual binding modes: Combined empirical and computational studies of a series of compounds showed adenine and 1‐benzyl‐4‐(dimethylamino)pyridinium fragments to function most efficiently in binding CHOKα1, and also determined how the latter fragment interacts with the choline binding site through two different binding modes. These data provide a basis for the future design of better and more selective inhibitors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>